2013
DOI: 10.1016/j.ssresearch.2012.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of marital quality in an arranged marriage society

Abstract: Drawing on a uniquely large number of items on marital quality, this study explores the determinants of marital quality in Chitwan Valley, Nepal. Marital quality is measured with five dimensions identified through exploratory factor analysis, including satisfaction, communication, togetherness, problems, and disagreements. Gender, education, and spouse choice emerge as the most important determinants of these dimensions of marital quality. Specifically, men, those with more schooling, and those who participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
78
1
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 51 publications
9
78
1
14
Order By: Relevance
“…This finding parallels with the findings of Çınar (2008), Günay (2007), Güven (2005); yet does not parallel with findings of Allendorf and Ghimire (2012), Anar (2011Anar ( ), Çakır (2008; Ng et al (2008). This situation can be explained with the fact that assessment of quality of marriage does not change in terms of gender.…”
Section: Discussionsupporting
confidence: 64%
“…This finding parallels with the findings of Çınar (2008), Günay (2007), Güven (2005); yet does not parallel with findings of Allendorf and Ghimire (2012), Anar (2011Anar ( ), Çakır (2008; Ng et al (2008). This situation can be explained with the fact that assessment of quality of marriage does not change in terms of gender.…”
Section: Discussionsupporting
confidence: 64%
“…Based on the result of the study they conducted, Şendil and Korkut (2012) stated that the general quality of marriage of individuals reduces with the increase in the number of children. According to Allendorf and Ghimire (2013), having children may cause conflict among partners regarding the responsibilities of parenting. In their study, Akbolat and Işık (2008) found that the number of children affects the emotional and mental burnout of their parents.…”
Section: Results Discussion and Suggestionsmentioning
confidence: 99%
“…It should also gain social recognition, which is realized through the wedding, a form of social announcement of a couple's marriage in front of the couple's family members, relatives, friends, colleagues, acquaintances, etc (Lin, et al, 2017;Wong, 2003). The wedding is the most common social phenomenon, but as a social convention, it entails economic costs (Allendorf & Ghimire, 2013;Carrington, 2002;Quinn, 2007). In South Korea, many families spend excessively for the wedding ceremony, through negotiations between the couple's families.…”
Section: Introductionmentioning
confidence: 99%